百度试题 结果1 题目Solve for x (5x-4)^(1/2)-x=0( ((5x-4))^(12)-x=0) 相关知识点: 试题来源: 解析 Graph each side of the equation. The solution is the x-value of the point of intersection. ( x=1,4)反馈 收藏
Solve for x given 5x−43+5=12x−1. Answer and Explanation: You can get rid of a fraction by multiplying by the denominator. For example, multiply the entire expression by 3, and you would have: 15x - 4 + 5 = 3/2x -1 Then you could get rid of the 2 in the...
Solve for x 5x-3=2x+9( 5x-3=2x+9) 相关知识点: 方程 一元一次方程相关概念 解一元一次方程 常规解法 试题来源: 解析 Move all terms containing ( x) to the left side of the equation.( 3x-3=9)Move all terms not containing ( x) to the right side of the equation.( 3x=12)Divide ...
Solve for x 5x+x^2>100 Subtract100100from both sides of theinequality. 5x+x2−100>05x+x2-100>0 Convert theinequalityto anequation. 5x+x2−100=05x+x2-100=0 Use thequadratic formulato find thesolutions. −b±√b2−4(ac)2a-b±b2-4(ac)2a ...
Solve for x: 5^(log x) + 5x^(log 5) =3 (a>0) 02:34 The number of solutions of "log"("sin"x)(2^(" tan"x)) gt 0 in the inte... 02:57 The set of real values of x for which 2^("log"(sqrt(2))(x-1)) gt x+... 04:20 Find the number of solution to equation...
Problem4.Solveforx:5x^2=10x-4 .⑧ (5±√5)/5 ⑧ )2 3/5(C)(5+2√5)/5(D)(3±2√3)/5(E)(5±2√3)/33±2√35±25(D)(E)53 相关知识点: 试题来源: 解析 (A).5x^2=10x-4=0x+4=0 . a =5, b=-10, and c=4. x_1=(-b±√(b^2-4ac))/(2a)=(-(...
Answer to: Solve for x: 5x + 8 = 3x - 10 By signing up, you'll get thousands of step-by-step solutions to your homework questions. You can also...
a) log(0.5)(x^(2)-5x+6) ge 1 rArr 0 lt x^(2)-5x+6 le(0.5)^(-1) rArr 0 lt x^(2) -5x+6 le2 {{:(x^(2)-5x+16 gt 0 rArr x^(2)-5 gt 1),(log(4)(x^(2)-5) lt1 rArr 0 lt x^(2)-5 lt 4):} rArr 1 lt (x^(2)-5) lt 4 rArr6 lt x^(2) ...
5x+7=±√25x+7=±2 The completesolutionis the result of both the positive and negative portions of thesolution. Tap for more steps... First, use the positive value of the±to find the first. 5x+7=2 Subtract7from both sides of the. ...
Solve for x -5x=-10( -5x=-10) 相关知识点: 试题来源: 解析 Divide each term in ( -5x=-10) by ( -5).( (-5x)/(-5)=(-10)/(-5))Cancel the common factor of ( -5).( x=(-10)/(-5))Divide( -10) by ( -5).( x=2)...